Influence of Suction on Capacity of Pile Foundation - Aizhan Sagu; Alfrendo Satyanaga; Nurly Gofar; Sonny Irawan; Ruslan Khamitov; Sung-Woo Moon; Jong Kim (Applied Sciences, 2023)
In the common practice of geotechnical design, the state of soil is considered fully saturated, while recent examples show the importance of the consideration of unsaturated conditions as well due to the location of the groundwater table at deeper levels. However, it is problematic to design a foundation and calculate bearing capacity as the internal stress in unsaturated conditions needs to be quantified. The mechanics of unsaturated soils are critical in geotechnical engineering, especially when the case of the foundation design is required. This study aims to investigate the influence of suction on the shaft capacity of pile foundations based on the data obtained from in situ and laboratory testing. The three modified methods (i.e., modified α, β, and λ) were implemented in this study in order to calculate the shaft capacity of the pile foundation incorporating unsaturated soil mechanics principles. In addition, the effect of varying matric suction on shaft capacity was discussed. The results of obtained changes show the importance of rain infiltration in the design of piles in unsaturated conditions. It can be concluded that the most conservative method is found to be the modified β method in designing pile foundations incorporating the suction changes due to rainwater infiltration. However, cost optimization shall be considered while choosing the method for the design. As for the increase in GWT, the modified <semantics>λ</semantics> method depicted the most conventional behavior. The possible rain infiltration decreases matric suction, mostly in the upper layers.